Between the Fact and the Construct. On the Epistemological Difficulties of a Historian - Brzozowski, Franciszek (Sensus Historiae, 2021)
The article presents an overview of selected methodological concepts in the area of history, showing the difficulties in the field of epistemology that affect the research practice of historians. The author focuses on the concept of truth in the context of accessibility to the past as a subject of research. The article also presents a fragmentary outline of the problem of the opposition between historical realists and constructivists as well as between fact and construct. The aim of the work is to present the difficulties that appear to be hard to overcome, especially for beginning researchers.